2022
DOI: 10.1007/s13762-022-04651-5
|View full text |Cite
|
Sign up to set email alerts
|

Air quality improvement assessment and exposure risk of Shandong Province in China during 2014 to 2020

Abstract: As one of the most polluted provinces in China, air pollution events occur frequently in Shandong. Based on the hourly (or daily) concentrations of six air pollutants (PM 2.5 , PM 10 , O 3 , NO 2 , SO 2 and CO), the situations of air quality improvement in three kinds of cities (key cities, coastal cities and general cities) are assessed comprehensively during 2014–2020. Contrary to the daily maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Table 1 shows the occurrence frequencies of individual criteria pollutants as the main pollutant in Hami and Turpan from 2018 to 2022. Unlike eastern China, where PM 2.5 , NO 2 , and O 3 were typical main pollutants [34,35], PM 10 was the most frequent main pollutant in eastern Xinjiang, followed by PM 2.5 and O 3 . In Hami and Turpan, the occurrence frequencies of PM 10 as the main pollutant were 63.1% and 74.1%, respectively, which is much higher than that in eastern Chinese cities (e.g., Shanghai, 5.00%) [34].…”
Section: Air Quality and Main Pollutantsmentioning
confidence: 88%
See 1 more Smart Citation
“…Table 1 shows the occurrence frequencies of individual criteria pollutants as the main pollutant in Hami and Turpan from 2018 to 2022. Unlike eastern China, where PM 2.5 , NO 2 , and O 3 were typical main pollutants [34,35], PM 10 was the most frequent main pollutant in eastern Xinjiang, followed by PM 2.5 and O 3 . In Hami and Turpan, the occurrence frequencies of PM 10 as the main pollutant were 63.1% and 74.1%, respectively, which is much higher than that in eastern Chinese cities (e.g., Shanghai, 5.00%) [34].…”
Section: Air Quality and Main Pollutantsmentioning
confidence: 88%
“…A similar increasing trend of O 3 has also been observed in eastern China. For example, in Lianyungang, a coastal city, the annual average concentration of O 3 increased by 0.92 µg•m −3 •yr −1 from 2015 to 2018; a continuous upward trend with a growth rate of 3.50% yr −1 was observed in Shandong from 2014 to 2020 [35,47]. Although the O 3 pollution in eastern Xinjiang has not attained the level in eastern China, its rapid growth indicated that a combined pollution of PM and O 3 might become the main situation of air pollution in eastern Xinjiang.…”
Section: Diurnal Weekly and Monthly Variationsmentioning
confidence: 99%